Parental Knowledge and Awareness of Autism Symptoms and Management Strategies - Afkar Fadhil Kareem; Abdulmutalib Abdulla Mohammed; Husham Hussain Abdul Ra’aoof; Ali Malik Tiryag (Academia Open, 2025)
Background: Usually manifesting in early childhood, autism spectrum disorder (ASD) is a neurodevelopmental disorder that impacts social communication and behavior. Objectives: The present study aims to contribute to raising awareness about autism spectrum disorder (ASD) through my research on assessing parents’ knowledge and awareness of its symptoms and management strategies. Methods: A cross-sectional study was conducted on a sample of 100 parents (both fathers and mothers) of children with autism spectrum disorder (ASD) to assess their knowledge of ASD symptoms, management strategies, and awareness levels. The sample was collected from the My Family Center for Autism in Basrah city. The questionnaire was distributed to the parents and collected approximately one week later. The collected data were then analyzed statistically, yielding the following results. Results: It was found that 80% of the parents had a moderate to good level of knowledge regarding ASD management strategies, while 20% had poor knowledge. For ASD symptoms, 75% showed moderate to good awareness, and 25% had poor understanding. The ratio of correct to incorrect answers per parent was approximately 3:1 for both parts of the questionnaire. Conclusion: Most parents demonstrated acceptable knowledge about ASD management strategies, and also most showed sufficient awareness of its symptoms. However, the remaining parents with lower knowledge levels require targeted educational programs to improve their understanding and support for children with autism spectrum disorder. Highlights: High parental awareness of ASD symptoms and management was observed. 75–80% of parents had moderate to good knowledge levels. Educational programs are needed for parents with low ASD awareness. Keywords: Knowledge, Awareness, Parents, Children, Autism Spectrum Disorder